The jurisdiction and power of shariah court in Malaysia: An analysis - Md Dahlan, Nuarrual Hilal (2007)
The jurisdictions of Shariah Court, except with regard to Shariah Court in the Federal Territories which only the Parliament has the power to pass law relating to it,are specifically provided in the respective States' Enactments of the Administration of lslamic Law.The power of the States to pass and make laws relating to Administration of lslamic Law,is originally conferred by Article 74(2) of the Federal Constitution (FC)and further this position has been entrenched in List II under the Ninth Schedule to the Federal Constitution (FC). However, based on the decisions of several case-law in Malaysia it is found that though the jurisdiction of the Shariah Court is clear on and over the said matters as conferred by the statutory provisions, yet there are certain enumerated matters which are still could not be decided freely and independently by the Shariah Court.These matters instead, have fallen into the realm of the Ordinary Civil Courts.It is contended that,this uncertainty would result in 'chaos' on the Shariah Court's jurisdiction and power to freely determine over its own matters.This phenomenon could shroud in uncertainty over and fetter the exclusiveness and entrenched jurisdictions and powers of the Shariah Court itself, which could even, arguably, reach the pinnacle of neglecting the significant of Article 121(1A)of the FC, in which, this provision has specifically ousted the Ordinary Civil Courts from interfering with the jurisdictions of the Shariah Court over certain exclusive matters.This paper will highlight the issues and will suggest certain measures in order to promote and upgrade the status and due functions of the Shariah Court in Malaysia.